Making decisions about hormone replacement therapy. Issue 7384 (8th February 2003) - Rymer, Janice; Wilson, Ruth; Ballard, Karen
Abstract : Many women will at some stage consider taking hormone replacement therapy, but uncertainty about the risks and benefits makes this decision difficult